2023
DOI: 10.3390/en16052117
|View full text |Cite
|
Sign up to set email alerts
|

Photovoltaic Module Degradation Forecast Models for Onshore and Offshore Floating Systems

Abstract: The degradation trend of photovoltaic modules depends on the technology, manufacturing techniques and climatic conditions of the site where they are installed. Longer useful life of the PV modules means that they will be able to produce much more energy than was used to build them; thus, extending the useful life of the modules is beneficial for the environment and increases the cost effectiveness of PVs. The problem of land use has prompted the development of agrivoltaic systems to exploit the same land both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 20 publications
0
1
0
Order By: Relevance
“…While the aforementioned efficiency gains are significant, some losses may be encountered due to a thin layer of salt that remains after the s.w. layer evaporation on the PV module, which may lead to a reduction in the solar irradiance reaching the PV cells [60]. Long-term exposure to humid and saline environments can lead to corrosion, potentialinduced degradation (PID), and other PV degradation effects reducing the module and system lifetime [19,21,60,61].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While the aforementioned efficiency gains are significant, some losses may be encountered due to a thin layer of salt that remains after the s.w. layer evaporation on the PV module, which may lead to a reduction in the solar irradiance reaching the PV cells [60]. Long-term exposure to humid and saline environments can lead to corrosion, potentialinduced degradation (PID), and other PV degradation effects reducing the module and system lifetime [19,21,60,61].…”
Section: Discussionmentioning
confidence: 99%
“…layer evaporation on the PV module, which may lead to a reduction in the solar irradiance reaching the PV cells [60]. Long-term exposure to humid and saline environments can lead to corrosion, potentialinduced degradation (PID), and other PV degradation effects reducing the module and system lifetime [19,21,60,61]. Biofouling effects, including algae growth on PV modules, may pose additional challenges [62,63].…”
Section: Discussionmentioning
confidence: 99%
“…Kim et al (Kim et al, 2021) discussed different types of degradation, accelerated-stress tests, levels, and prioritization to expand the life expectancy of the PV module by means of IEC 61215 (The standard qualification test programs for terrestrial photovoltaic modules). Mannino et al (Mannino et al 2023), reported the preliminary study of evaluating the influence of marine environmental variables on the degradation trend of photovoltaic modules. Onshore and offshore environmental variables are used as input for the degradation forecast model and subjected to numerical simulations to obtain quantitative results.…”
Section: Figure 12mentioning
confidence: 99%
“…Mannino et al [47] conducted a study focused on developing degradation forecast models for PV modules in both onshore and offshore floating systems. This investigation is particularly relevant as floating PV panels can be deployed on lakes and dams, providing a solution to land use challenges for other purposes.…”
Section: Solar Energy Applicationsmentioning
confidence: 99%